Repellent Activity of Catnip Extract (Nepeta cataria L,) Against Aedes aegypti Mosquito as Dengue Vector - Doraysamy Doraysamy; Budi Mulyaningsih; Ernaningsih Ernaningsih (Pusat Kedokteran Tropis, 2012)
ABSTRACTIntroduction: Dengue infection has been a major concern for decades. Prevention from getting bitten by Aedes aegypti mosquito is considered better than cure as there is no specific antiviral treatment for dengue. Recently, catnip (Nepeta cataria L.) extract has been formulated and marketed as an alternative for protection against mosquitoes and act as a natural form of mosquito repellent.Objectives: To understand the repelling properties of both DEET and N. cataria L. extract and to compare the repelling properties between DEET and N. cataria L. against Ae. aegypti mosquito.Methods: The repelling properties was tested based on the number of mosquitoes that sits on the hand of the respondent after being applied to the gold standard of mosquito repellent, DEET, and compared to N. cataria L. extract in different concentrations in total of 15 minutes.Results: Three different concentrations of catnip extract (10%, 30% and 50%) shows different efficacy in repelling Ae. aegypti mosquitoes at the range of 62.8%-80%, although the repellent activity is still lower than DEET that have 100% repellent activity.Conclusion: Catnip (N. cataria L) showed mosquitoes repellent properties at concentration 10-50% with repellent activity at the range 62.8%-80%. Keywords: Dengue, Aedes aegypti, repellent, DEET (N,N- Diethyl-m-toluamide), catnip (Nepeta cataria L.) extract. INTISARI Pendahuluan: Infeksi Dengue merupakan masalah utama selama berpuluh tahun. Pencegahan dengan menghindari gigitan nyamuk Aedes aegypti dianggap lebih baik daripada mengobati karena tidak ada terapi antiviral yang spesifik untuk dengue. Akhir-akhir ini, ekstrak catnip (Nepeta cataria L.) telah diformulasi dan dipasarkan sebagai alternatif untuk perlindungan terhadap nyamuk dan berlaku sebagai bentuk alami dari repelen.Tujuan: Untuk memahami agen penolakan dari N,N- Diethyl-m-toluamide (DEET) dan ekstrak N. cataria L. extract dan membandingkan agen penolakan antara DEET dan N. cataria L. terhadap nyamuk Ae. aegypti.Metode: Agen penolakan diuji berdasarkan jumlah nyamuk yang mendarat di tangan responden setelah diolesi repelen nyamuk baku DEET, dan dibandingkan dengan ekstrak N. cataria L. pada berbagai konsentrasi selama total waktu 15 menit.Hasil: Tiga konsentrasi ekstrak catnip (10%, 30% and 50%) menunjukkan daya penolakan nyamuk Ae. aegypti yang berbeda pada rentang 62.8%-80%, meskipun aktivitas penolakan nyamuknya masih lebih rendah dari DEET yang mempunyai aktivitas penolakan 100%.Simpulan: Ekstrak Catnip (N. cataria L) menunjukkan daya penolakan nyamuk pada konsentrasi 10-50% dengan aktivitas repelant antara 62.8%-80%.Kata kunci: Dengue, Aedes aegypti, repellent, DEET (N,N- Diethyl-m-toluamide), ekstrak catnip (Nepeta cataria L.).